New TiTaNbZrMo high-entropy alloys for metallic biomaterials - Chenwei Li; Ying Ma; Xu Yang; Minghao Hou (Materials Research Express, 2021)
The advantages of high entropy alloy with good comprehensive properties provide a potential opportunity to explore and develop new alloys suitable for human implantation. In this experiment, TiTaNbZrMo high entropy alloy was designed and prepared by alloy design and first principle. The calculation results predict that the phase composition of each high entropy alloy is BCC structure, and the designed high entropy alloy has structural stability; the non-equal atomic ratio TiNbTaZrMo high-entropy alloy has higher ductility than the equal atomic ratio TiNbTaZrMo high-entropy alloy; the B/G, Poisson’s ratio υ and ( C _12 - C _44 ) values of Ti _30 (NbTaZr) _60 Mo _10 alloy are the largest, indicating that the toughness of this alloy is the best, and the Young’s modulus value is the smallest. The experimental results show that the yield strength of Ti _30 (NbTaZr) _60 Mo _10 alloy is 1132 MPa, the plastic strain is 33%, and the wear resistance and corrosion resistance are good. The potential of Ti _30 (NbTaZr) _60 Mo _10 in biological field is proved by calculation and experimental test, which provides an important basis for its industrial application in biomedical alloy.